Thought is Grievance: on Žižek's Parallax. - Butler, Rex (International Journal of Žižek Studies, 2010)
The author examines the pivotal concept of subtraction in light of the concept of grievance by philosopher Slavoj Žižek. He analysis Žižek's concept of symptom in the book "The Sublime Object of Ideology," and concept of parallax in his another book "The Parallax View." The work of Žižek is marked by a kind of constitutive split as the changes of mind or reversals of position updates the argument and shift in strategy in response to changing conditions. Žižek's aim of philosophy is to provide solutions.